LINC00601 promotes the progression of glioma via the p-STAT3 signaling pathway - Chao Ma; Linqi Wang; Renwu Zhang; Tong Li; Peng Li; Yuxiang Ding; Dejun Wu; Yinyan Wang (Cancer Cell International)
Abstract Background Gliomas, the most common malignant tumors of the central nervous system, primarily originate from glial cells, which support nerve cells. Due to their high malignancy and aggressiveness, gliomas frequently result in poor prognoses. Increasing evidence suggests that long non-coding RNAs (lncRNAs) have diverse roles in cancer; however, their specific functions in gliomas remain poorly understood. This study elucidates the roles and potential mechanisms of the lncRNA LINC00601 in glioma. Methods Bioinformatics analysis was utilized to identify the expression of LINC00601 and to perform related survival analysis. Glioma cells were transfected with a control vector small interfering RNA (si-NC) or small interfering RNA LINC00601 (si-LINC00601). Cell proliferation was evaluated using the CCK-8 assay and plate colony formation assay. Cell migration and invasion were assessed using the Transwell assay. Protein expression was detected by Western blot analysis, and lncRNA levels were measured using quantitative real-time PCR (qRT-PCR). Results Bioinformatics analysis revealed that LINC00601 is associated with the pathological grade and prognosis of glioma, as evidenced by data from the TCGA and CGGA databases. In vivo experiments showed that LINC00601 knockdown inhibits the proliferation, migration, and invasion of U251 and U87 cells. Based on sequencing and Western blot results, this effect is thought to be linked to changes in Phosphorylated Signal Transducer and Activator of Transcription 3 (p-STAT3) expression. Additionally, in vitro knockdown of LINC00601 has been shown to inhibit glioma growth. Conclusions LINC00601, which facilitates glioma progression by modulating the p-STAT3 signaling pathway, could serve as a potential molecular target for glioma therapy.